A Modified Wagner Stem Design Increases the Primary Stability in Cementless Revision Hip Arthroplasty - Julius M. Boettcher, MSc; Kay Sellenschloh, Dipl. Ing; Gerd Huber, Dr.; Benjamin Ondruschka, Professor; Michael M. Morlock, Professor (Arthroplasty Today)
Background: Primary stability is of great importance for the longevity of the implant in cementless revision total hip arthroplasty, since instability is a major cause of rerevision. The purpose of this study was to evaluate the effect of an additional set of less prominent, wider splines added to an established conical stem design with sharp splines on axial stability in a model with significant proximal bone defects. Methods: Twenty fresh-frozen human femurs were implanted with either the established or the additional spline design, dynamically loaded and tested in a load-to-failure configuration. Cortical contact in the femoral canal after implantation was evaluated by superimposing computed tomography scans and 3-dimensional laser scans. Stem subsidence and micromotion were evaluated to assess primary stability. Results: Stems remained stable during cyclic loading of up to 200% body weight, except in bones with cortical bone mineral density below 1000 mgHA/mL. A significant reduction of more than 85% in stem subsidence (P = .040), axial micromotion (P = .007), and rotational micromotion (P = .010) was achieved with the new spline design. Load-to-failure testing exceeded 400% body weight. Conclusions: The new spline design increased the cortical contact which resulted in increased axial primary stability in this in vitro experiment. Bone mineral density as a measure of bone quality proved to be a decisive factor for achieving immediate postoperative stability. Further variations of the established stem designs could further improve the longevity of artificial joint replacements.